ANALISA KONSEP OBJECT ORIENTED PROGRAMMING PADA BAHASA PEMROGRAMAN PHP - Kadek Wibowo (Universitas Bina Sarana Informatika, 2015)
In making computer application an important role is the language of programming, without any programming language not be called off computer application desired. Of all languages programming computers that is , programming language based object be a language very popular of creation program computer application. A programming language this is pretty flexible and easy to is modified into an a display that is interesting windows based. Programming language oriented object or object-oriented programming ( oop ) is an approach programming use object and class. Php at first the script is just a collection of simple. With progress in , then added a variety of programming features oriented object. This was initiated since php 4. With the emergence of php 5 , programming features oriented object the more steadily and the sooner. With php 5 , script using the concept object-oriented will be quickly and more efficient.Keywords: programming languages, object-oriented programming (OOP)